Characterization of Chittagong Aerosol by PCA Modeling (Journal of Bangladesh Academy of Sciences, 2012)
Black carbon and other selected trace elements concentrations in aerosol samples collected at   the Continuous Air Monitoring Station (CAMS) in Chittagong, the second largest city in Bangladesh, were investigated for possible source contributions. The particulate matter (PM) sampling was done from end of winter to middle of rainy season (February and July, 2007) using dichotomous sampler. The samples collected in two fractions of